Strengthening Information and Control Systems The Synergy Between Information Technology and Accounting Models - Mancini, Daniela; Dameri, Renata Paola; Bonollo, Elisa (Lecture Notes in Information Systems and Organisation,, 2016)
This book presents a collection of original research papers focused on the relationship between information technology and accounting and control models. The book discusses the importance of establishing a synergetic relationship between new information technologies (ERP, BI, web-based technology, data mining, XBRL, etc.) and new or renewed accounting models and tools (performance indicators, prevision and simulation models, accounting models for public administration, etc.) in order to enhance an organization's capability to manage information and make valuable decisions. The search for these synergies takes place at all organizational levels: at a strategic level, in order to simulate and forecast behaviors and financial results at a management level, in order to innovate performance measurement and improve value creation at the operational level, in order to improve information quality and the efficiency of the information process. This book is particularly useful for IS and CFO managers and scholars, as it is based on a selection of the best papers - original, double blind reviewed contributions - presented to the Annual Conference of the Italian Chapter of AIS under the category "Accounting Information Systems".